Influence of hearing loss and cognitive abilities on language development in CHARGE Syndrome. Issue 8 (4th May 2016) - Vesseur, Annemarie; Langereis, Margreet; Free, Rolien; Snik, Ad; van Ravenswaaij‐Arts, Conny; Mylanus, Emmanuel
Abstract : Hearing loss and cognitive delay are frequently occurring features in CHARGE syndrome that may contribute to impaired language development. However, not much is known about language development in patients with CHARGE syndrome. In this retrospective study, hearing loss, cognitive abilities, and language development are described in 50 patients with CHARGE syndrome. After informed consent was given, data were collected from local medical files. Most patients (38.3%; 18/47 patients) had moderate hearing loss (41–70 dB) and 58.5% (24/41 patients) had an IQ below 70. The mean language quotients of the receptive and expressive language were more than one standard deviation below the norm. Both hearing loss and cognitive delay had an influence on language development. Language and cognitive data were not available for all patients, which may have resulted in a pre‐selection of patients with a delay. In conclusion, while hearing thresholds, cognitive abilities and language development vary widely in CHARGE syndrome, they are mostly below average. Hearing loss and cognitive delay have a significant influence on language development in children with CHARGE syndrome. To improve our knowledge about and the quality of care we can provide to CHARGE patients, hearing and developmental tests should be performed regularly in order to differentiate between the contributions of hearing loss and cognitive delay to delays in language development, and to provide adequate hearing amplification in the case of hearing loss. © 2016 Wiley Periodicals, Inc.